Motivation Engineering to Employee by Employees Abraham Maslow Theory - Joko Suyono; Sri Wiwoho Mudjanarko (STKIP Singkawang, 2017)
Among many existing motivational theories, perhaps Maslow's Hierarchy of Needs Theories are widely known. This theory passes a message to us that once a person passes a certain level of need, he is no longer motivated by the level of motivation below. This provides an understanding that a manager or leader or motivator in the organization should know what is needed by subordinates. The need of a daily production worker with staff of managerial staff is different. To provide motivation that can improve performance to both, a motivator must provide different treatment according to their needs.